2020
DOI: 10.1177/0950017020919670
|View full text |Cite
|
Sign up to set email alerts
|

Do Equal Qualifications Yield Equal Rewards for Immigrants in the Labour Market?

Abstract: Using a correspondence field experiment, the study reported in this article has investigated if immigrant job applicants with equivalent qualifications are treated differently in the Finnish labour market. The study consists of 5000 job applications that were sent out to 1000 advertised positions by five applicants of Finnish, English, Iraqi, Russian and Somali backgrounds, who differed only in their names. The findings show that applicants of immigrant origin receive significantly fewer invitations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Russian speakers were especially distressed about the economic consequences and uncertainty of the situation. In Finland, Russian speakers have a better socio-economic standing compared with Somali and Arabic speakers, many of whom have refugee backgrounds and face more discrimination in the job market [ 22 ]. Thus, the distress of our Russian-speaking respondents may reflect their ‘fear of falling’: the relatively wealthy are more concerned about economic instability than are those with lower incomes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Russian speakers were especially distressed about the economic consequences and uncertainty of the situation. In Finland, Russian speakers have a better socio-economic standing compared with Somali and Arabic speakers, many of whom have refugee backgrounds and face more discrimination in the job market [ 22 ]. Thus, the distress of our Russian-speaking respondents may reflect their ‘fear of falling’: the relatively wealthy are more concerned about economic instability than are those with lower incomes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This population group is generally young: approximately 44% are under 20 years of age, and less than 9% are over 49 [ 18 ]. Several studies have reported that Somalis in Finland commonly face discrimination and racism in their everyday lives [ 21 ] and in the labour market [ 22 ]; their unemployment rate has remained high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This viewpoint indicates that the occupational attainment process of HSMs can be seen as their efforts to make capital out of resources and capital formation results from the dynamics between such efforts and the host country's labour market structure. The empirical study presented in this article opposes a pessimistic view that HSMs of the non-Western origin are naturally subject to discrimination or overqualification when seeking employment in a host country (see Ahmad 2020). But it is by no means supporting an optimistic perspective that HSMs are always able to get a job in a host country owing to their competence.…”
Section: Job-seeking Intentionmentioning
confidence: 63%
“…This is also applied to the case of foreign students in Finland, in which the Finnish language and cultural knowledge on the Finnish working life are used to screen out the job application of international students (Alho 2020). In addition, white migrants from the Western European continent or North America are more likely to be accepted than non-white migrants from the non-Western countries (Ahmad 2020;Alho 2020;Koskela 2014). Koskela (2014: 27) furthers this discussion by identifying the linkage between ethnicity and employment in Finland, such as Indian IT or African cleaners.…”
Section: The Finnish Labour Marketmentioning
confidence: 99%